ANALISIS DAN PENGEMBANGAN SISTEM INFORMASI PENERIMAAN MAHAMAHAMAHASISWA BARU BERBASIS CODEIGNITER PHP FRAMEWORK - Fitriyani, Fitriyani; H.M Yusuf, Zakaria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This study aims to develop a New Student Admissions Information System Based on Codeigniter PHP Framework. This software serves to simplify the process of registering new students who so far still use paper documents and Microsoft Excel. This study also aims to test the software based on McCall's quality factors which include correctness, reliability, efficiency, integrity, and usability. This research method is Research and Development. The development model used is Waterfall which consists of analysis, design, implementation, and testing. The data in this study were obtained from: (1) the correctness test using the KLOC calculation; (2) reliability testing using Blitz, Loader, LoadImpact, and Blazemeter; (3) efficiency testing using Pagespeed Insights, YSlow, Pingdom Tools, and Websitetest; (4) integrity testing using Acunetix and Netsparker; and (5) usability testing using the PSSUQ (Post-Study System Usability Questionnaire) questionnaire on fifty one respondents including lecturers, academic administration and students at Jabal Ghafur University.Keywords: Information Systems, Admission of New Students, CodeIgniter, McCall